A SOCIOLOGY OF LAW AND (RE) DESIGNING A LEGAL REALITY - Kustura, Mensur; Karo, Emina (International Scientific Journal Vision, 2018)
Sociology of law is not a static science discipline, it changes as right and changes are happening ever faster. It is not limited to what constitutes only the law, rules and institutions, but encompasses all the more or less colored rights - legal and social injustice. Since this is the right, which is derived from the pluralism of legal sources, but only partially legitimate sources, a more dynamic subject that is problematic to comprehend. The difficulties grow even if the right as such is not observed, is not through the form of legal science interpreted, but in the dominant understandings of the applicable law. But that is the task of sociology of law. It deals really with the real right, as well as with the real application of rights, and with the reality whose regulation is the purpose of modern law. These three areas of ontology of rights are not always clearly separated. The difficulties faced by sociologists to investigate the right, due to the fact that they are viewed in a practical context as legitimate right, have actually been increased rather than diminished. This is more fully manifested in the example of legal reality as the reality of the application of legitimate rights. For political reality, as a reality of the emergence of legal norms, nothing less is to be divided into a public and shady reality. For reality, whose decor is the purpose of law, this dichotomy has always been considered a characteristic. Under the light of the discursive public, the actors manifest their dedication to the law; violation of the law, however, happens latently. It is therefore complex to explore the valid law in “light” and “shadowy”, and thus the research of sociology of law is constantly confronted again.